On the need for individualisation in physical education - Józef Węglarz (University of Applied Sciences in Tarnow, Poland, 2018)
Individualisation in the process of physical education is a contemporary challenge. The forms of conducting classes used so far, based on collective, most often homogeneous effort without taking into account the diverse abilities of students, do not stand the test of time. This may cause problems, mainly in terms of behaviour, as the student's rights at school have been strengthened and his/her dissatisfaction with the programme has an impact on the course of the didactic process. It is necessary to think in advance about possible manifestations of such reluctance or lack of acceptance of the proposed offer so that the authority of the school does not suffer and the pupils are satisfied that the offer meets their expectations. This will be possible when the curriculum of physical education takes into account, more than before, the needs of the individual.